1995
DOI: 10.1111/j.1570-7458.1995.tb01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on chromatin supraorganization, nuclear phenotypes, and survival of Triatoma infestans

Abstract: The nuclear phenotypes and survival of the hemipteran, Triatoma infestans (Hemiptera, Reduviidae), were studied in specimens treated with copper sulfate and methylmercury. The objective was to determine whether changes in chromatin supraorganization and insect survival similar to those promoted by other stressing agents could also be induced by heavy metals. At the concentrations used, copper sulfate and methylmercury were toxic to the cells, mainly inducing nuclear degeneration in the Malpighian tubules and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The unpackaging of heterochromatin, a phenomenon that was previously reported as a cellular survival response to stress factors in the Malpighian tubules of Triatomini (Mello et al, 1995(Mello et al, , 2001, was observed under all tested conditions. However, the frequency of nuclei with heterochromatin unpackaging one and 48 h following the 5-AZA treatment exceeded the frequency observed in the untreated controls or in DMSO-treated nymphs.…”
Section: Cytidine Demethylation Assaymentioning
confidence: 71%
See 2 more Smart Citations
“…The unpackaging of heterochromatin, a phenomenon that was previously reported as a cellular survival response to stress factors in the Malpighian tubules of Triatomini (Mello et al, 1995(Mello et al, , 2001, was observed under all tested conditions. However, the frequency of nuclei with heterochromatin unpackaging one and 48 h following the 5-AZA treatment exceeded the frequency observed in the untreated controls or in DMSO-treated nymphs.…”
Section: Cytidine Demethylation Assaymentioning
confidence: 71%
“…In addition, the T. infestans chromocenters are able to unpack under stressful conditions such as prolonged starvation, heat or cold shock, and the presence of heavy metals (Mello, 1989;Mello et al, 1990Mello et al, , 1995Mello et al, , 2001Campos et al, 2002). This finding may indicate activation of genes usually silent and contained in the chromocenter body (Mello et al, 1990).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the participation of these factors has not generally been demonstrated in Artemia, experimental data collected in other organisms reveals their existence. For instance, in NIH 3T3 mouse cells treated with valproic acid produce decondensation in the chromatin structure of the nucleus, including the heterochromatin areas (Felisbino et al, 2014); while in Malpighian tubule cells of the blood-sucking insect, Triatoma infestans, heterochromatin decondensation occurs either after treatments with heavy metals (copper and mercury) or heat shocks (Mello et al, 1995(Mello et al, , 2001). Moreover, heterochromatin decondensation after heat shock treatements in Malpighian tubule cells of a vector of Chagas' disease in Brazil, Panstrongylus megistus, infected and non-infected by Trypanosoma cruzi, has been also reported (Garcia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, when examining responses of liver polyploid cells to in-flammatory cytokines such as interferon gamma (IFN-gamma), diploid, tetraploid, and octoploid hepatocytes are equally susceptible to IFNgamma-induced apoptosis (Martin et al 2002). No comparable data exist for invertebrate cell, although insect Malpighian tubules may also be involved with detoxifying mechanisms (layered "concretions" − Mello et al 1995).…”
Section: Introductionmentioning
confidence: 99%